Factors Affecting the Intention to Donate Money for Wakaf Among Civil Servants in the Ministry of Religious Affairs in Banjarnegara Regency - Widodo, Jennifer Selviana; Darma, Emile Satia (Journal of Accounting and Investment, 2025)
Abstract: Research aims: This study examine the factors that influence the intention of cash waqf for the state civil apparatus of the ministry of religion of the banjarnegara district by examining the influence of accountability, transparency, crowfunding platform security and the reputation of the Indonesian waqf agency.Design/Methodology/Approach: This study involved the state civil apparatus of the ministry of religion in banjarnegara district. Hypotheses were tested using SEM-PLS techniques.Research findings: The results showed that transparency and accountability did not have a significant positive effect on the intention of state civil servants to endow money. while the security of the crowfunding platform and the reputation of the Indonesian waqf agency have a significant positive effect on the intention to endow money.Theoretical contribution/Originality :The novelty of this research is to exploreand comprehensively analyze how the influence of accountability, transparency, crowfunding platform security & reputation of the Indonesian waqf agency builds cash waqf intentions for state civil apparatus at the ministry of religion.Practitioner/Policy implication : Based on this insight, it is hoped that building cash waqf intentions for the state civil apparatus is not only in the ministry of religion but is comprehensive for all ministries and city / district governments. Indonesian waqf agencies as managers of cash waqf funds can carry out all tasks by considering accountability, transparency, crowfunding platform security and reputation.Research limitation/Implication: The implementation of transparency, accountability, crowfunding platform security and reputation, the main purpose of which is to build intention to donate money, is still insufficiently implemented. In addition, the underlying process of how Badan Wakaf Indonesia collects and presents cash waqf information is crucial.